Analisis Perbandingan Karbon Aktif Tempurung Keluak (Pangium Edule) dan Karbon Aktif Komersial dengan Aktivator HCl dan KOH dalam Menurunkan Cr (VI) dan Cu (II) pada Limbah Elektroplating - Ramadhani, Fajar Tegar; Mohamad Mirwan (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
The electroplating process, also known as electrocoating or metal plating, is a technique used to coat the surface of a solid material with a layer of metal through the application of an electric current in an electrolyte solution. This study utilized keluak shell biomass as an adsorbent in a fixed-bed column. The objective of this research was to analyze the adsorption capacity of keluak shell in reducing Cr⁶⁺ and Cu2+ concentrations. The research method employed was experimental, using electroplating wastewater obtained from an industry in Sidoarjo. The study was conducted with activated carbon derived from keluak shells, activated with 1 M HCl and 5% KOH solutions, as well as commercial activated carbon for comparison. The variations were based on sampling times of 30, 60, 90, and 120 minutes. The results showed that the application of keluak shell biomass activated with 1 M HCl, 5% KOH, and commercial activated carbon as adsorbents yielded optimal concentration reductions of Cr⁶⁺ 23.9 mg/L; Cu2+ 0.7593 mg/L; Cr⁶⁺ 56.8 mg/L; Cu2+ 0.7593 mg/L; Cr⁶⁺55.4 mg/L; Cu2+ 0.7593 mg/L, respectively. These values were obtained at 30 and 60 minutes sampling intervals, where the initial adsorption rate was relatively high due to the unoccupied surface of the adsorbent, thereby enhancing removal efficiency.